Penerapan Manajemen Peserta Didik dalam Meningkatkan Prestasi Non Akademik di SMP Negeri 2 Rengasdengklok Karawang - Alin Ratna Rengganis; Ahmad Junaedi Sitika; Debibik Nabilatul Fauziah (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
Student management is the arrangement and arrangement of activities related to students from entering school to becoming alumni. Student management activities are an important part of an educational institution that must be considered. So that in its implementation, student management affects the potential development and achievement of students in schools, both academic and non-academic achievements, such as developing potential in certain fields by participating in extracurricular activities at SMP Negeri 2 Rengasdengklok. non-academic fields through the development of students' interests and talents through extracurricular activities. SMP Negeri 2 Rengasdengklok does not only focus on academic achievement, but also focuses on potential non-academic achievements, because this school understands that not all students are able to master activities in the academic field, but some of them have abilities in the non-academic field. This research method uses descriptive qualitative research by conducting interviews with the vice principal and teachers. The results of this study indicate that the planning, implementation and evaluation of student management in improving students' non-academic achievement at SMP Negeri 2 Rengasdengklok has been carried out well. This can be seen from the indicators regarding student management, such as the formation of a new student admissions committee, recruitment, selection, orientation, placement, reporting and student development.